Beyond conferences and journal publications: Publishing and presenting research online through a virtual poster session - Renner, Angelika; Baeseman, Jenny (Septentrio Conference Series, 2014)
The Virtual Poster Session (VPS), developed by the Association of Polar Early Career Scientists (APECS), is an open access online tool for publishing conference posters and discussing the research presented through posters outside the traditional conference environment. Instead of having posters collect dust or confining them to an archive on a computer’s hard drive after they were presented at a conference, they can be uploaded and displayed on the APECS website, with each poster having a unique webpage link. There, they can be accessed from any computer with an internet connection, and others can comment and contact the author. Additional monthly online seminars give the authors of these posters the opportunity to present their research live to an international and interdisciplinary audience and respond to questions and feedback. In these sessions, scientists can hone their presentation and discussion skills in a friendly and informal setting as well as publicize their research even further. Currently, over 200 posters by authors and co-authors from 34 countries are accessible through the APECS website (http://www.apecs.is/virtual-poster-session). Over 30 of these posters have been presented in live Virtual Poster Sessions to date, centered on themes such as research areas, countries, and post-meeting round-ups. The audience during the calls included early career and senior scientists, educators, journalists and others. The calls provide useful opportunities to talk to an international and interdisciplinary audience irrespective of location or funding situation. Online tools such as the VPS create ways to open up new collaborations to discuss research ideas, and to share results and methodologies outside the restrictions of national, financial, and disciplinary boundaries.